2023
DOI: 10.3390/microorganisms11071789
|View full text |Cite
|
Sign up to set email alerts
|

A Severe Acute Respiratory Syndrome Coronavirus 2 Anti-Spike Immunoglobulin G Assay: A Robust Method for Evaluation of Vaccine Immunogenicity Using an Established Correlate of Protection

Mingzhu Zhu,
Shane Cloney-Clark,
Sheau-line Feng
et al.

Abstract: As the COVID-19 pandemic continues, variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continue to emerge. Immunogenicity evaluation of vaccines and identification of correlates of protection for vaccine effectiveness is critical to aid the development of vaccines against emerging variants. Anti-recombinant spike (rS) protein immunoglobulin G (IgG) quantitation in the systemic circulation (serum/plasma) is shown to correlate with vaccine efficacy. Thus, an enzyme-linked immunosorbent assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Receptor hACE2 binding inhibition levels were observed to be correlated with virus neutralization titers in mice [13]. Previous studies reported a correlation between IgG titers of spike antigen binding and receptor hACE2 binding inhibition, as well as between hACE2 binding inhibition and neutralizing antibody titers in human blood samples [26][27][28]. This study in a mouse model suggests that a strategy of multivalent COVID-19 vaccination might be applicable for inducing effective immunity.…”
Section: Discussionsupporting
confidence: 60%
“…Receptor hACE2 binding inhibition levels were observed to be correlated with virus neutralization titers in mice [13]. Previous studies reported a correlation between IgG titers of spike antigen binding and receptor hACE2 binding inhibition, as well as between hACE2 binding inhibition and neutralizing antibody titers in human blood samples [26][27][28]. This study in a mouse model suggests that a strategy of multivalent COVID-19 vaccination might be applicable for inducing effective immunity.…”
Section: Discussionsupporting
confidence: 60%
“…For correlation with anti-S IgG antibodies and hACE2 binding inhibition, the samples were tested using a validated anti-S IgG assay (Clinical Immunology, Novavax) and using a previously published method [ 15 ] or a validated hACE2 binding inhibition assay (Clinical Immunology, Novavax) [ 16 ], followed by comparison of the data with the PNT results using linear regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For the analysis of difference of SRRs, based on an assumption of 80% SRR for NVX-CoV2373 and 85% SRR for NVX-CoV2515, there was 90% power to conclude noninferiority with a margin of −5% (NVX-CoV2515 relative to NVX-CoV2373). Participant serum antibody concentrations were measured via a previously validated assay [ 18 ].…”
Section: Methodsmentioning
confidence: 99%